2016
DOI: 10.1159/000443399
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an Early Discontinuation of Thyroid Hormone Treatment in Very-Low-Birth-Weight Infants at Risk for Transient or Permanent Congenital Hypothyroidism

Abstract: Background/Aims: This prospective study was conducted to investigate the feasibility of an early discontinuation of thyroid hormone treatment in very-low-birth-weight (VLBW) infants with congenital hypothyroidism (CH). Methods: We enrolled VLBW infants between January 2011 and December 2012. The infants were divided into the hypothyroid and normal thyroid function groups according to the results of a thyroid function test. We performed an early off-therapy trial at 24 months of age. Results: Of the 182 VLBW in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
(61 reference statements)
0
14
0
1
Order By: Relevance
“…Recent studies have advocated that the course of CH is transient in many premature babies where discontinuing thyroxine supplementation is possible before 3 years of age (55,56). A recent study showed that infants with CH requiring lower L-thyroxine doses (<3.25 µg/kg) are likely to have transient CH, and thus might be re-evaluated at 12 or 24 months rather than 3 years of age (57).…”
Section: Evidence Not To Treat Thopmentioning
confidence: 99%
“…Recent studies have advocated that the course of CH is transient in many premature babies where discontinuing thyroxine supplementation is possible before 3 years of age (55,56). A recent study showed that infants with CH requiring lower L-thyroxine doses (<3.25 µg/kg) are likely to have transient CH, and thus might be re-evaluated at 12 or 24 months rather than 3 years of age (57).…”
Section: Evidence Not To Treat Thopmentioning
confidence: 99%
“…The majority of VLBW patients diagnosed with hypothyroidism were weaned off treatment by 24 months of age in some studies [35, 36]. All our patients were on treatment at discharge from NICU.…”
Section: Discussionmentioning
confidence: 99%
“…These results warrant further research to better understand the underlying causes of this high incidence and whether our single-center experience is reflective of the rates of hypothyroidism in VLBW infants across Lebanon. Although most of those newborns may prove to have transient hypothyroidism [35, 36], vigilance in screening and in obtaining second sample screenings is necessary in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Re-evaluation is possible before 3 years of age in preterm infants. Lim et al [57] and Jung et al [58] reported that discontinuation of thyroxine supplementation is possible at the age of ≤2 when low doses of levothyroxine administration could be successfully maintained.…”
Section: Issues On Thyroid Hormone Replacementmentioning
confidence: 99%